2009
DOI: 10.1021/jf9031684
|View full text |Cite
|
Sign up to set email alerts
|

Combination Treatment with Luteolin and Quercetin Enhances Antiproliferative Effects in Nicotine-Treated MDA-MB-231 Cells by Down-regulating Nicotinic Acetylcholine Receptors

Abstract: Large-scale epidemiological cohort studies performed in the United States indicate that breast cancer risk is associated with active and passive smoking. As of yet, however, there is no direct evidence of antitumor effects by agents that block the effect of tobacco compound nicotine (Nic) on relevant nicotinic receptors (nAChR) involved in breast tumorigenesis. In the present study, the expression profiles of different nAChR subunits in the human breast cancer cell line (MDA-MB-231) were characterized by RT-PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 33 publications
2
54
0
Order By: Relevance
“…Chiang et al reported that luteolin significantly suppresses the growth of MCF-7 and MDA-MB-435 breast tumor in vitro (17). Shinh et al reported that luteolin significantly decreased MCF-7 and MDA-MB-231 breast tumor growth in vitro (18). We have shown that the viability of MCF-7 cells was inhibited by luteolin after 72 h of treatment in a time-dependent (P=0.02) and concentration-dependent manner (P=0.04).…”
Section: Discussionmentioning
confidence: 99%
“…Chiang et al reported that luteolin significantly suppresses the growth of MCF-7 and MDA-MB-435 breast tumor in vitro (17). Shinh et al reported that luteolin significantly decreased MCF-7 and MDA-MB-231 breast tumor growth in vitro (18). We have shown that the viability of MCF-7 cells was inhibited by luteolin after 72 h of treatment in a time-dependent (P=0.02) and concentration-dependent manner (P=0.04).…”
Section: Discussionmentioning
confidence: 99%
“…1) (4). These signaling pathways are closely correlated to the formation of several cancers; in particular, a7-nAChR is associated with lung (5), bladder (6), and colon cancers (7), and a9-nAChR is associated with breast cancer (8)(9)(10) (Fig. 1).…”
Section: Biological Functions Of Nicotinic Acetylcholine Receptorsmentioning
confidence: 96%
“…Furthermore, nicotine has been shown to induce activation of NF-kB through the MAP kinase p38 and PI3K/AKT signaling pathways, promoting the survival, proliferation, and angiogenesis of ECs (32). Another study showed that AKT survival signals play an important role in the nicotinemediated carcinogenic process in human breast cancer cells (10).…”
Section: Nachr-mediated Signaling Pathwaysmentioning
confidence: 99%
“…Quercetin (Que), an nAChR antagonist, was found to inhibit the proliferation of human breast cancer cells through blockage of Nic receptors and nAChR subunit expression. 5 Que is a component of most edible fruits and vegetables, with the highest concentrations found in onions, apples, and red wine. 6,7 Although the anticancer mechanisms are not yet fully understood, current evidence demonstrates that Que is beneficial for improving breast cancer chemotherapy and is a potential chemopreventive agent.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Although the anticancer mechanisms are not yet fully understood, current evidence demonstrates that Que is beneficial for improving breast cancer chemotherapy and is a potential chemopreventive agent. 5 However, the poor water solubility of Que leads to its minimal absorption in the gastrointestinal tract, and its oral bioavailability (BA) is 17% in rats and only 1% in men. 8,9 Que was previously applied in early-stage clinical trials as an anticancer agent; however, it required the use of solvents such as dimethyl sulfoxide (DMSO) or ethanol.…”
Section: Introductionmentioning
confidence: 99%